Cardiac beriberi: morphological findings in two fatal cases - Othman Mohammad; Riezzo Irene; Neri Margherita; Bello Stefania; Turillazzi Emanuela; Fineschi Vittorio (BMC, 2011)
Abstract Cardiovascular beriberi is categorized into two main groups, according to its cause: alcoholic and non-alcoholic (dietary). Cardiovascular beriberi can also be divided into a fulminant form (Shoshin beriberi) and a chronic form. Shoshin beriberi is characterized by hypotension, tachycardia, and lactic acidosis and is mainly encountered in non-alcoholic patients in Asian countries, although it has also been seen in alcoholics in Western countries. Due to the complex clinical presentation and to the lack of diagnostic tests, thiamine deficiency is still being missed, especially among non-alcoholics patients. We present two fatal cases of non - alcohol associated cardiac beriberi. An acute myocardial infarction was observed in one case; extensive colliquative myocytolisis (grade 2) was described in the second case respectively. Morphologically, myocardial necrosis and colliquative myocytolysis are the histologic hallmarks of this acute, rare clinical entity. An increase in apoptotic myocytes was demonstrated probably sustaining the cardiogenic shock.